Surface defect chemistry of Y-substituted and hydrated BaZrO3 with subsurface space-charge regions. Issue 19 (26th April 2016) - Polfus, Jonathan M.; Bjørheim, Tor S.; Norby, Truls; Bredesen, Rune
Abstract : First-principles calculations were utilized to elucidate the complete defect equilibria of surfaces of proton conducting BaZrO3, encompassing charged species adsorbed to the surface, defects in the surface layer as well as in the subsurface space-charge region and bulk. Abstract : First-principles calculations were utilized to elucidate the complete defect equilibria of surfaces of proton conducting BaZrO3, encompassing charged species adsorbed to the surface, defects in the surface layer as well as in the subsurface space-charge region and bulk. Defect calculations were performed for the BaZrO3 (0 0 1) surface with focus on protons, oxygen vacancies and Y-acceptor dopants as well as adsorbed hydroxide and oxide adions. Protons were found to exhibit a particularly strong tendency to segregate to the surface with a segregation energy of −1.3 eV. While the concentration of negatively charged Y-acceptors and hydroxide species on the outer surface can be quite high, they do not fully charge compensate the protons, yielding a net positive charge of the surface. The resulting surface potential can exceed 1 V, resulting in significant depletion of charge carriers in the subsurface space-charge region. Moreover, the results are discussed in relation to surface adsorption of water, and computational approaches for treating charged point defects in periodic slab cells are evaluated with respect to symmetry and charge compensation.